AssessmentThe Impact of Early Childhood Development Capitation on ECDE Programme in Kenya: A Case of Narok South Sub County, Kenya - Shinali, Mary Consolata; Githui, Millicent; Thinguri, Ruth; Koech, Peter (Journal of Education and Practice, 2014)
The study looked at the assessment of the Early Childhood Development capitation grant on ECDE centres in Narok south Sub County. The main objective of this study was to assess the impact of capitation grant on ECD in the centres under study. The basis of the study was on a conceptual framework on the objectives of ECDE curriculum in Kenya and how the capitation grant fund enhanced the achievement of the holistic development. Descriptive survey design was used. Qualitative and quantitative data collection techniques were combined and used. The instruments used were questionnaires, observation checklist and structured interview. Purposive sampling was used in the selection of the population where 50 respondents from 20 ECDE centres were selected for the study. The data that was analyzed was presented in tabular and graphical form. The researcher established that the ECD capitation grant has led to an increase in the enrollment of learners in ECDE centers, there was adequacy of the teaching and learning materials and this in turn has enhanced learning despite the fact that the grant was considered inadequate. The community should be sensitized on the ECDE capitation grant so that it is not mistaken with Free Primary Education (FPE). Consequently, parents will offer support and demand for accountability from the administration. The government should employ early childhood development (ECD)teachers as a motivation to ensure efficiency in their delivery. The study will be of significance to the Ministry of Education and the development of ECD in Narok Sub-county. The management committee of the ECDE capitation grant will solicit for more funds to improve on the teaching and learning environment. The ministry of education will get assistance on how the funds have been utilized and improve the running of the ECDE capitation funds.
Keywords: capitation grant; early childhood development education programmes; Kenya